Study of Aloe vera combined with PAC Application for Reducing Pollutants in Water - Temmy Wikaningrum; Yaniza Dela Daza (Jurnal Serambi Engineering, 2024)
Poly Aluminum Chloride (PAC) is a chemical that is frequently utilized in the treatment of drinking water. It is therefore essential to investigate methods of reducing the dosage of PAC in conjunction with natural ingredients that have the potential to adsorb pollutants in water. This research employs a combination of PAC and aloe vera, utilizing the optimal composition identified in previous research. The research was conducted on a laboratory scale using raw water samples of river water that had been intentionally contaminated with iron. The pollutant parameters measured were iron, organic matter, and ammonia. These parameters were selected as they are likely to be affected by the addition of aloe vera. The results of the treatment using jar tests were evaluated by comparing the quality of the initial water sample, the use of PAC alone, and the use of a combination of PAC and aloe vera. The experimental results demonstrated that the combination of PAC and Aloe vera exhibited superior efficacy in reducing iron levels compared to PAC alone. However, this combination also resulted in a notable increase in organic matter levels in the water samples.